Towards 1D nanolines on a monolayered supramolecular network adsorbed on a silicon surface. Issue 24 (8th June 2016) - Makoudi, Younes; Beyer, Matthieu; Lamare, Simon; Jeannoutot, Judicael; Palmino, Frank; Chérioux, Frédéric
Abstract : We successfully achieved the formation of bilayered networks on a silicon surface including 1D nanolines in the second layer by deposition of a tailored molecule on a silicon surface. Abstract : The growth of 3D extended periodic networks made up of π-conjugated molecules on semi-conductor surfaces is of interest for the integration of nano-components in the future generations of smart devices. In the work presented in this article, we successfully achieved the formation of bilayered networks on a silicon surface including 1D-isolated nanolines in the second layer. Firstly, we observed the formation of a 2D large-scale supramolecular network in the plane of a silicon surface through the deposition of tailored molecules. Then using the same molecules, a second-layer, based on 1D nanolines, grew above the first layer, thanks to a template effect. Mono- or bi-layered networks were found to be stable from 100 K up to room temperature. These networks were investigated by scanning tunnel microscopy imaging under an ultra-high vacuum (UHV-STM).